Avaliação do período de jejum pré-abate e do sexo sobre as características de carcaça em avestruzes (Struthio camelus) - Eduardo Castanheira de Mello (2010)
We evaluated the effects of four periods (15, 20, 25 and 30 hours) of pre-slaughter fasting on weight loss and carcass yield in ostriches (Struthiocamellus). Were used sixty-four ostriches (thirty-two males and thirty-two females) of the Black African race, created by the fourteen months of age. These birds have been separated from a lot coming from 256 pups born in the same week, where four days before slaughter were distributed according to the fasting period (treatments) and gender. In all treatments (15, 20, 25 and 30 hours) fasting was only water. The experimental design was completely randomized design with 2x4 factorial arrangement (two genders versus four fasting times), eight repetitions per treatment. For comparisons involving the gender factor was used t-test at 5% probability and the analysis of fasting time was made a regression analysis. Were analyzed the following variables: hot carcass yield, cold carcass yield, pH value after two hours cooling retail cut of Fan Fillet and Big Drum and yield of edible viscera such as liver and heart. There was no significant difference between treatments (P>0.05), however, the period of 15 hours of fasting provided the higher yield of hot and cold carcass, 51% and 50.60% respectively when compared to other treatments. The pH of the ostrich meat was not influenced by different periods of fasting before the slaughter (P>0.05), thereby maintaining the quality of the final product, was observed in the Fan Fillet the average pH of 5.94 and the Big Drum pH 5.89. Was significant difference between gender (P<0.05), where males had better carcass weight with average weight of 46.14 kilograms since the females 43.98 kilograms. And the Retail Visceras such as heart and liver the fasting period of 15 hours had the higher yield compared to other treatments (P<0.05).